Investigation of intersexual polled goats - Bordán, Judit; Kovács, András; Bodó, Szilárd (Acta Agraria Debreceniensis, 2015)
The sex reversal may occur in all mammalian species, but is connected to a favourable trait – the polledness – only in the goat. Later abnormal sex ratio was noticed in these goat populations, in which a part of the phenotypically male individuals was sterile. These males have two X chromosomes. In goats the PIS (Polled Intersex Syndrome) mutation is responsible for the absence of horns in homozygous and heterozygous individuals. This same mutation causes a female-to-male sex reversal, but only in the homozygous polled genetic female goats. The PIS mutation inhibits the expression of the FOXL2 gene which is responsible for ovary development, and a protein encoded by this gene inhibits the activity of the Sox9 gene. The Sox9 gene stimulates the development of the cells of the testis. When the FOXL2 gene is inhibited, the Sox9 gene is activated and transforms the ovary cells into testis cells. In our article we briefly introduce the morphological and chromosome investigations of three intersex individuals we found.